Hubungan Burnout Perawat yang Bertugas di Rawat Jalan dengan Kualitas Pelayanan Pasien - Ipung Muhamad Dhaifurrohman; Indah Sri Wahyuningsih; Suyanto Suyanto (Journal of Health, Medical, and Psychological Studies, 2026)
Burnout is a condition of physical, emotional, and mental exhaustion frequently experienced by nurses due to high work demands, particularly in outpatient units with large patient volumes and rapid service intensity. This condition can affect nurses’ performance, attitudes, and interactions in providing nursing care, thereby potentially reducing the quality of services perceived by patients. This study aimed to determine the relationship between burnout among outpatient nurses and the quality of patient services. This study employed a quantitative method with a cross-sectional design. The research population consisted of outpatient nurses and patients, with a sample of 20 nurses and 100 patients selected using purposive sampling techniques. Data were collected using a nurse burnout questionnaire measuring emotional exhaustion, depersonalization, and personal accomplishment, as well as a patient service quality questionnaire based on the dimensions of reliability, responsiveness, assurance, empathy, and tangibles. Data analysis was conducted using univariate and bivariate analyses with the Gamma test. The results showed that most outpatient nurses experienced a moderate level of burnout, while the majority of patients perceived the quality of services as high. Bivariate analysis indicated a significant relationship between nurses’ burnout levels and the quality of outpatient services. Lower levels of nurse burnout were associated with better quality of services perceived by patients.